Tanatogénesis y utopía. Vera Weiler (comp.). Figuraciones en proceso. Santafé de Bogotá, Universidad de Colombia, Universidad Industrial de Santander, Fundación Social, 1998 - Alzate Echeverri, Adriana (Estudios Políticos, 1998)
Reseña